SISTEM PENGUPAHAN PEKERJA PADA USAHA KERUPUK MULIENG DI KABUPATEN PIDIE : (Analisis Perspektif Ekonomi Islam) - Safwan (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2020)
This research aims to examine how the system of hired mulieng cracker business workers in Pidie Regency as well as the islamic economic review related to it. To that end, the author conducted interviews with mulieng cracker workers and entrepreneurs. The writing of this thesis uses a descriptive method of analysis, and the results of the data obtained are qualitatively analyzed. The results showed that the wage system for workers based on habits that have been in force since hereditary in the area, where employers provide workers wages ranging from Rp. 12,000 to 17000 per bamboo. The wage system applied by employers to their workers is not all in accordance with the wage system in the view of the Islamic economy, because it has not been able to meet the needs of their daily lives. Whereas Islam has regulated the wage system using three principles, namely the principle of justice, the principle of worthiness and the principle of virtue. Therefore, it can be concluded that the system of hired workers of mulieng cracker business workers has not fulfilled the principles of feasibility and virtue well. However, the authors suggest that the government continues to work to increase concern for mulieng cracker workers,especially arrangements on fair and adequate workers' wages, so as not to harm both employers and workers..